THE ROLE OF ISLAMIC STUDIES IN STRENGTHENING RELIGIOUS MODERATION - Dian Permana; Avivaty Zahriyah; Asmarita; Asnawi Malik; Mahin Ainun Naim (PT. Cadas Insan Madani, 2026)
Religious moderation has become an increasingly important approach for fostering social harmony, peaceful coexistence, and national unity in multicultural societies. In the face of globalization, digital transformation, and the rapid dissemination of religious information through social media, communities are challenged by the spread of intolerance, extremism, and religious polarization. Within this context, Islamic Studies plays a strategic role in promoting a comprehensive understanding of Islamic teachings that emphasize justice, balance (wasatiyyah), tolerance, mutual respect, and peaceful coexistence. This study aims to examine the role of Islamic Studies in strengthening religious moderation by analyzing its conceptual foundations, educational functions, and contributions to developing inclusive and harmonious societies. The research employed a qualitative library research approach using scholarly books, peer-reviewed journal articles, policy documents, and official publications related to Islamic Studies and religious moderation. The collected data were analyzed through descriptive content analysis to identify key themes concerning the integration of moderation values within Islamic scholarship and education. The findings indicate that Islamic Studies contributes significantly to strengthening religious moderation by promoting contextual interpretations of Islamic teachings, encouraging critical thinking, developing interreligious understanding, and fostering ethical and civic responsibility. Furthermore, Islamic educational institutions serve as important platforms for cultivating moderate religious attitudes through curriculum development, character education, dialogue, and community engagement. The study concludes that strengthening religious moderation requires collaborative efforts among educational institutions, religious scholars, policymakers, and communities to ensure that Islamic Studies continues to promote inclusive, peaceful, and compassionate values in addressing contemporary social challenges. Therefore, Islamic Studies should be positioned as a strategic instrument for building resilient, tolerant, and socially cohesive societies in the twenty-first century.